PENGEMBANGAN DESAIN DIDAKTIS PENALARAN SPASIAL DAN PENALARAN KUANTITIF DALAM MATERI TEOREMA PYTHAGORAS DI SMP - Ernawati, Ernawati; Suratman, Dede; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract  The background of this research was the lack of junior high school students’ spatial reasoning and quantitative reasoning  in Pythagoras theorem. This research used Didactical Design Research (DDR) method which started by a preliminary study to 18 students of grade IX A Bumi Khatulistiwa  Junior High School.  The preliminary study was aimed to explore students’ learning obstacles to develep didactical design. The developed didactical design was implemented to 20 students of grade VIII A of Bumi Khatulistiwa  Junior High School. After this implementation the developed didactical design was revised. The results of this research were the learning tools used by previous teacher have  explored spatial reasoning and quantitative reasoning, the developed didactical design had minimized students’ epistemological obstacle.    Keywords: Didactical Design, Spatial Reasoning, Quantitative Reasoning, Epistemogical Obstacle